Permutation methods a distance function approach - Mielke Paul W; Bery Kenneth J (New York Springer-Verlag, 2007)
This edition places increased emphasis on the use of alternative permutation statistical tests based on metric Euclidean distance functions that have excellent robustness characteristics. These alternative permutation techniques provide many powerful mul
Keywords: Resampling(Statistics); Statistical hypothesis testing